Lieutenant Katia - Devilliers, Catherine; Haldane, Charlotte, 1894-1969. (London : Constable, 1964)
Tells the amazing experiences of a French girl in the Russian Army during World War II.
Keywords: Devilliers, Catherine; Soviet Union. -- Armiia. -- Engineers, 10th.; World War, 1939-1945 -- Campaigns -- Eastern Front -- Personal narratives, French